Systemic toxicity evaluation of novel tobacco products in Caenorhabditis elegans. (February 2020) - Cai, Haiqing; Xu, Yilu; Tang, Shen; Yang, Xiaobo; Zou, Yunfeng; Wang, Xinhang; Mo, Laiming; Wu, Bin; Liang, Ziwei; Li, Yunqing; Wei, Xuejing; Ao, Qingqing; et al.
Abstract: Under strictly Framework Convention on Tobacco Control, novel tobacco products are going to be promising alterations to consumers and manufactures. Even though the novel tobacco products have been considered less harmful than traditional tobaccos, there is a few knowledges about the subsequent substances during consume and their impacts to the consumers due to short introduction into the market. Thus, the present study aims to investigate the adverse effects of novel tobacco products on Caenorhabditis elegans ( C. elegans ) and to provide relevant references for novel tobacco products toxicity research and assessment. C. elegans individuals at L4 stage were exposed to different kinds of novel tobacco products, including electronic cigarettes liquid (e-liquid), the extract of e-cig aerosol (e-aerosol), mint and black tea flavor snus. After specific exposure time, the multiple toxic endpoints of C. elegans were measured, including acute toxicity, locomotion behavior, body length, and life-span. The oxidative stress was tested too. According to acute toxicity assays, the half lethal dose of four novel tobacco products calculated from theoretical nicotine concentration, ranked as follows e-liquid (0.29 mg/ml) > the extract of e-cig aerosol (0.43 mg/ml) > mint flavor snus (1.20 mg/ml) > black tea flavor snus (1.50 mg/ml). The equivalent lethal rate 5% 20% of four novel tobacco products were applied to following experiments. These novel tobacco products damaged nematode's locomotion including head thrashing and body bending, the damage was most evident in two flavors of snus. The similar trends were found in reproductive performance investigation. At tested concentrations, the retardation development of C. elegans was found throughout all stages with peak blockage at adulthood. Life-span tests showed that novel tobacco products at 5% lethal rate seemed no significant effect on affected the life-span of nematodes, with snus shortened the lifespan of C. elegans at 20% lethal rate. Imaging stress response indicted four types of tobacco productions causing stress response in C. elegans . Exposed to either 5% or 20% lethal levels (5% and 20%), the percentages of worms with DAF-16 redistribution among all groups varied, with higher frequencies in both snus. Summary, novel tobacco products caused multiple adverse impacts to C. elegans, including acute toxicity, locomotion behavior disruption, brood size reduction, development retardation, and life-span reduction. The toxicity was associated with both the feature and concentration of tobacco products, and oxidative stress was the main mechanism. Highlights: There has been no comprehensive investigation on multiple toxic endpoints induced by different novel tobacco products so far. The present study revealed that the novel tobacco products caused multiple adverse consequences. The response level to lethal dose was introduced to different toxicity tests due to the complexity of by-products from novel tobacco products. Another focus of concern should be snus, which showed more harmful outcomes than other novel tobacco products.